Macroeconomic trends and reforms in Germany - Roberto Sabbatini; Francesco Zollino (PSL Quarterly Review, 2010)
This paper traces the main macroeconomic developments in the German economy from national unification. Its performance is compared with that of the rest of the euro area and its largest economies. The study documents as Germany’s modest growth in the later 1990s  was due to the restrictive impact on domestic demand coming from the deep restructuring and modernization of the production system, followed by sweeping reforms after the turn of the century. Rapid productivity increases and prolonged wage moderation, especially in industry, fuelled a large and mounting current account surplus in Germany, that compares with the deficits registered in most European countries. The study retraces the recent debate on how to correct those imbalances, recalling the arguments for and against the thesis that the countries with a current payments surplus, above all Germany, must also play an active role in fostering the adjustment of the deficit countries. A possible synthesis is proposed, based on an analysis of the formation of national income and the use of resources according to the national accounts system. The implication is that Germany may contribute to the correction of imbalances within the euro area not so much by altering the wage formation mechanism as by creating incentives for domestic investment, hence fostering employment creation, in the service sectors that are currently lagging behind the extraordinary perfomance of a number of core activities in the industry.